PENGARUH PEMBERIAN AIR KELAPA DAN TRICHOKOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) TERHADAP PERTUMBUHAN BIBIT KARET STUM MATA TIDUR KLON PB-260 - Prasetyo, Agus; Nurhidayah, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The objective of this research is to determine the interraction of giving coconut water and trichokompos oil palm empty bunch and the best combination of treatment for the growth of the eye stum rubber bed. The research was conducted at Experimental Station, Faculty of Agriculture, University of Riau on March 2017 until June 2017, implemented by Randomized Complete Design (RAL) Factorial consisting of 2 factors and 3 replications. The first factor is the provision of coconut water (A) consists of 3 levels: A1 (250 cc.l-1 water), A2 (500 cc.l-1 water), A3 (750 cc.l-1 water). The second factor is the provision of trichokompos (B) consists of 3 levels: B1 (100 g per polybag), B2 (200 g per polybag), B3 (300 g per polybag). Each unit consists of 2 plants there are 54 plants. Parameters measured were time buds appear (days), shoot length (cm), number of leaves (pieces), shoot diameter (cm) and shoot dry weight (g). The result of the variance were continued by Duncan multiple distance test at 5% level. The results showed combination treatment with coconut water giving 750 cc.l-1 water and trichokompos 200 g per polybag showed the best results for the time parameter appearing shoots, shoot length, number of leaves, stem diameter and dry weight of shoots. Keywords: Stum sleep eyes, coconut water, oil palm empty bunch trichokompos